2004
DOI: 10.1021/es049919z
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradability, DBP Formation, and Membrane Fouling Potential of Natural Organic Matter:  Characterization and Controllability

Abstract: Various natural organic matter (NOM) constituents were evaluated in terms of their biodegradability, disinfection byproduct (DBP) formation potentials, and membrane fouling. The biodegradability of NOM was evaluated with respect to biodegradable dissolved organic carbon (BDOC) and its inhibition control. NOM was divided into (i) colloidal and noncolloidal NOM, using a dialysis membrane with a molecular weight cutoff of 3500 Da and (ii) hydrophobic, transphilic, and hydrophilic NOM constituents, using XAD-8/4 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(37 citation statements)
references
References 16 publications
3
33
0
1
Order By: Relevance
“…One important reason is that a water layer could be easily formed on a hydrophilic surface and foulants with hydrophobic property are repellent to the surface. But it should be clarified that in certain situations hydrophilic membranes are more inclined to attract hydrophilic substances and thus induce fouling (Kwon et al, 2005). There are a number of ways to increase membrane surface smoothness as well as hydrophilic property, such as surface modifications, novel materials and synthesis process, etc.…”
Section: Surface Modificationmentioning
confidence: 99%
“…One important reason is that a water layer could be easily formed on a hydrophilic surface and foulants with hydrophobic property are repellent to the surface. But it should be clarified that in certain situations hydrophilic membranes are more inclined to attract hydrophilic substances and thus induce fouling (Kwon et al, 2005). There are a number of ways to increase membrane surface smoothness as well as hydrophilic property, such as surface modifications, novel materials and synthesis process, etc.…”
Section: Surface Modificationmentioning
confidence: 99%
“…Disinfection byproduct formation potential during the HA degradation process was assessed according to the literature [3,23]. Various HA solutions were adjusted to pH 7 with an appropriate buffer and chlorinated (30 mg/L) using concentrated NaClO solution.…”
Section: Procedures and Analysismentioning
confidence: 99%
“…It has been found that various constituents in DOM pool have different DBP formation potentials (Kitis et al 2001;Nikolaou and Lekkas 2001;Kwon et al 2005;Chow et al 2005). The knowledge of DOM profile in terms of DBP formation potential is critical to DBP control in water treatment processes.…”
Section: Introductionmentioning
confidence: 99%